Nannoplankton Biostratigraphy from Banggai-Sula Basin, Central Sulawesi - Nurhidayah, Efrilia Mahdilah; Akmaluddin, Akmaluddin; Barianto, Didit Hadi; Husein, Salahuddin; Saripudin, Asep (Universitas Gadjah Mada, 2024)
The nannoplankton research was conducted in the MH-2 well, Banggai-Sula Basin, Central Sulawesi. Thirty-four ditch-cutting samples were utilized to observe the Minahaki, Kintom, and Biak Formations. Age determination was carried out using biostratigraphy method and standard procedure for first and last occurrence of nannoplankton biodatum and had an absolute age, widely known as a zone indicator. This study aims to determine the age and nannoplankton biozonation of each geological formation in Banggai-Sula Basin. Based on the biostratigraphic analysis, 39 species from 14 genera with abundance frequencies ranging from rare to abundant were found in the MH-2 well. In this study, new results of the age of Banggai-Sula Basin areMiddle Miocene – Early Middle Pliocene (13,706 – 3,727 Ma), and can identify into six calcareous nannoplankton zones that are more detailed than previous researchers, Discoaster signus zone (NN5), Discoaster exilis zone (NN6-NN7), Discoaster berggrenii zone (NN11), Ceratolithus acustus zone (NN12), Helicosphaera sellii zone (NN13-NN15), and the Discoaster tamalis zone (NN16). Biostratigraphic data also shows new information for the first time, the absence of three zones from zone NN8 to zone NN10. This result indicates an unconformity in the Late Miocene age (10.606–8.20 Ma).